Alfiyah Ibn Malik’s Learning Transformation of Queen Al-Falah Mojo Kediri Islamic Boarding School During the Covid-19 Pandemic - Nurul Hanani; Ahmad Sapto Hudoyo (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2021)
The transformation of educational patterns is essential and must continuously be updated to adapt to the circumstances and needs. With the Covid-19 pandemic, Islamic boarding schools have felt a significant impact, so they are forced to carry out traditional transformations in their daily lives because pesantren is a place to practice togetherness in large-scale implementation in every aspect activity. With regulations issued by the government, Islamic boarding schools are forcibly repatriating students to avoid the spread of COVID-19. However, gradually pesantren are getting permission to do offline learning again with certain conditions. This phenomenon attracted the author to research one of the famous Islamic boarding schools in Keidiri, which aims to discover the transformation of Alfiyah Ibn Malik's learning activities with new customs. This research is in the form of action research using a qualitative approach. The results of the study showed a significant change in the learning process of Alfiyah Ibn Malik.